Paul Louis Landsberg : el potencial sanador de la mirada : silencio y primacía de la contemplación, su significación en la antropología medieval - Mosto, Marisa (Sapientia, 2021)
The work aims to highlight the primacy of contemplation for the moral growth of the person. It takes as a starting point the article by Paul Louis Landsberg "The Middle Ages and us" and proposes some categories of the anthropology of san Agustín and santo Tomás as windows of understanding and complementation of Landsberg's proposal.